2018
DOI: 10.3899/jrheum.171362
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Forced Vital Capacity and Lung Diffusion Cutpoints for Associated Radiographic Interstitial Lung Disease in Systemic Sclerosis

Abstract: Objective Forced vital capacity (FVC) and carbon monoxide diffusion (DLCO) are used for systemic sclerosis-associated interstitial lung disease (SSc-ILD) screening. The study purpose was to determine the sensitivity, specificity, and negative predictive value (NPV) (proportion of true negative screening tests) of FVC and DLCO thresholds for SSc-ILD on chest high-resolution computed tomography (HRCT) scans. Methods Patients fulfilling American College of Rheumatology 2013 SSc criteria with a chest HRCT scan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 14 publications
9
46
0
2
Order By: Relevance
“…Although pulmonary function tests (PFTs) are frequently used by rheumatologists as a screening test for ILD in their patients with SSc, studies have shown that they lack sensitivity for the detection of ILD in a general population of patients with SSc (4,7). For example, in a cross‐sectional study of 102 patients with SSc (41% with diffuse cutaneous SSc [dcSSc]) with a median disease duration of 6 years (interquartile range [IQR] 3–12.5 years), a forced vital capacity (FVC) <80% predicted had a sensitivity of only 37.5% for the detection of ILD on HRCT imaging (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although pulmonary function tests (PFTs) are frequently used by rheumatologists as a screening test for ILD in their patients with SSc, studies have shown that they lack sensitivity for the detection of ILD in a general population of patients with SSc (4,7). For example, in a cross‐sectional study of 102 patients with SSc (41% with diffuse cutaneous SSc [dcSSc]) with a median disease duration of 6 years (interquartile range [IQR] 3–12.5 years), a forced vital capacity (FVC) <80% predicted had a sensitivity of only 37.5% for the detection of ILD on HRCT imaging (4).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with an increasing body of literature indicating that PFTs are less sensitive than HRCT in detecting the presence of or assessing the severity of interstitial lung disease in CVID or collagen vascular diseases. [27][28][29] Combination immunosuppressive therapy induced long-lived remissions in the majority of patients. Excluding 2 patients who died and 1 who had a lung transplant, 9 of 36 patients (25%) had a relapse of GLILD when not undergoing immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For the Assassi et al data set (14), which was used as the training data set, patients were classified as having ILD when the percentage FVC predicted was less than 70%. For the Hinchcliff et al data set (5), which was used as validation cohort, ILD was defined as the presence of radiographic findings consistent with ILD in the opinion of an expert thoracic radiologist (5,51). The Cheadle et al data set (38), also used as a validation cohort, defined ILD according to pulmonary function tests and chest high-resolution computed tomography.…”
Section: Methodsmentioning
confidence: 99%